2015
DOI: 10.1016/j.jconrel.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal contributions to detoxification of acute pharmacotoxicity by a triglyceride micro-emulsion

Abstract: Triglyceride micro-emulsions such as Intralipid® have been used to reverse cardiac toxicity induced by a number of drugs but reservations about their broad-spectrum applicability remain because of the poorly understood mechanism of action. Herein we report an integrated mechanism of reversal of bupivacaine toxicity that includes both transient drug scavenging and a cardiotonic effect that couple to accelerate movement of the toxin away from sites of toxicity. We thus propose a multi-modal therapeutic paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 54 publications
6
109
0
Order By: Relevance
“…The need for lipemic plasma is based on the accumulating evidence that intravenous lipid emulsion functions both as a scavenging agent to accelerate redistribution of the offending drug [22][23][24][25][26] and as a direct inotrope to improve cardiovascular performance. 22,[27][28][29] The latter mechanism is consistent with the observation that small-volume infusions (40 mL/hour) of 20% Intralipid elevate blood pressure in healthy patients while only moderately increasing triglyceride concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The need for lipemic plasma is based on the accumulating evidence that intravenous lipid emulsion functions both as a scavenging agent to accelerate redistribution of the offending drug [22][23][24][25][26] and as a direct inotrope to improve cardiovascular performance. 22,[27][28][29] The latter mechanism is consistent with the observation that small-volume infusions (40 mL/hour) of 20% Intralipid elevate blood pressure in healthy patients while only moderately increasing triglyceride concentrations.…”
mentioning
confidence: 99%
“…The need for lipemic plasma is based on the accumulating evidence that intravenous lipid emulsion functions both as a scavenging agent to accelerate redistribution of the offending drug [22][23][24][25][26] and as a direct inotrope to improve cardiovascular performance. 22,[27][28][29] The latter mechanism is consistent with the observation that small-volume infusions (40 mL/hour) of 20% Intralipid elevate blood pressure in healthy patients while only moderately increasing triglyceride concentrations. [30][31][32] In accordance with these assumptions, we used a physiologically based pharmacokinetic-pharmacodynamic model that has been repeatedly back-tested against physiologic data 22,28,33 to estimate a rational infusion regimen needed to maintain a modestly lipemic plasma.…”
mentioning
confidence: 99%
“…ILE may have carried the stimulant drug from the heart and brain to less well-perfused organs (scavenging effect), and then once the concentration of caffeine was sufficiently low, ILE may have acted as a tonic to the depressed heart. Recent studies have suggested that ILE may act as a 'shuttle' to move drugs around the body-and not as a 'sink' that captures and isolates drugs [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, free fatty acids from the lipids provide a supportive energy source throughout detoxification. 13 These mechanisms of action help us understand how IFE supports cardiac function. However, this proposal of mechanism hasa few caveats when discussing its use specifically in TCA overdose.…”
Section: Discussionmentioning
confidence: 99%
“…The research undertaken and reviewed by Fettiplace et al 13 looked primary at bupivacaine, a long-acting anesthetic. Bupivacaine acts primary on voltage-gated sodium channels while TCAs have multiple cellular targets, thus their mechanism of toxicity is primarily different.…”
Section: Discussionmentioning
confidence: 99%